091 Multi-disciplinary team assessment of high risk patients with severe aortic valve stenosis leads to better than predicted survival, earlier tracheal extubation and shorter intensive care stay. (22nd September 2015) - Calvert, P A; Rafiq, I; Ozdemir, B; Watson, W; Hansom, S; McCormick, L; Rana, BS; Lee, E M; Dunning, J; Rusk, R A; Webb, S T; Klein, A A; et al.
Abstract : Introduction: Treatment of high risk patients with severe aortic valve stenosis has been revolutionised by Transcatheter Aortic Valve Implantation (TAVI). We hypothesise that multi-disciplinary team (MDT) assessment by cardiologists, cardiothoracic surgeons and anaesthetists facilitates appropriate case selection and achieves better than predicted outcomes in this high risk group. Methods: All patients (n=111) referred to the MDT for TAVI were prospectively enrolled. Baseline demographics and outcomes were recorded. Results are median (IQR) unless stated. Results: Patients (n=25) awaiting treatment/final MDT decision were excluded. Twenty patients were treated by TAVI (seven transfemoral, 13 transapical), 27 by conventional surgical AVR (csAVR), nine with balloon aortic valvuloplasty (BAV) and 30 medically. There were no differences in baseline characteristics (except for an excess of prior CABG surgery in the TAVI group vs csAVR (16/20 vs 3/27; p<0.001). There were no differences in logistic EuroSCORE (ES): TAVI: 19.8% (9.3–24.8%); csAVR: 12.1% (7.5–27.1%); BAV: 26.0% (12.8–37.5%); medical: 20.4% (10.6–40.0%): p=0.34. Thirty-day mortalities were: TAVI: 0/19; csAVR: 0/27; BAV: 1/9; medical: 8/30 (abstract 091 figure 1 ). Adjusting for ES, the observed/expected 30 day mortality indices were: TAVI: 0; csAVR: 0; BAV: 0.37; medical: 1.31. Patients receiving valve replacement (TAVI and csAVR) had lower 30-day mortality than those receiving palliative treatment (BAV and medical): 0% vs 23.1%, p<0.001. This survival benefit persisted upon medium-term follow-up, log rank p<0.001 (abstract 091 figure 2 ). TAVI patients had shorter intensive care unit (ICU) stays than csAVR patients: 22.0 (9.9–41.3) h vs 36.6 (23.3–169.2) h, p=0.03 and shorter durations of tracheal intubation: 2.1 (1.9–5.8) h vs 11.9 (8.6–20.1) h, p<0.001. There was a non-significant trend to shorter hospital stay in TAVI vs csAVR patients: 7 (6–11) days vs 11 (7–21) days, p=0.053. Outliers of hospital length of stay were defined from a cohort of all patients who underwent redo-cardiac surgery or conventional AVR surgery in the past 2 years (n=551). The 2.5th and 97.5th centiles were 1.8 and 38.4 days. On exclusion of patients outside these times (three patients from each group) there was a significant difference in hospital length of stay between the TAVI and csAVR groups: 7.0 (5.3–8.0) days vs 9.5 (6.3–17.3) days, p=0.015. Conclusion: MDT assessment of high risk patients with severe aortic valve stenosis combined with multi-modality treatment options results in lower than predicted mortality. Patients selected for TAVI have shorter ICU stays than patients selected for csAVR despite equivalent co-morbidities.